The role of electronic sports journalism in spreading the culture of sports professionalism in Algeria - zouaoui, Abdelouahab (sports creativity, 2025)
Despite its relatively short experience in the media field, Algerian online sports journalism contributes to raising awareness of sports in general and football in particular. It dedicates online media space to promoting sports programming on radio and television, as well as in its print and online publications, aiming to cultivate a culture of sports professionalism in Algeria. This includes introducing sports clubs in the first and second professional leagues and highlighting the importance and requirements of professionalism in sports programming. Various Algerian sports media outlets follow suit, especially after the 2012 advertising law, which explicitly opened the sector to private investment after it had been exclusively controlled by the public sector. This has led to the establishment of Algerian online sports media outlets, including radio, television, and print and online sports journalism. These diverse and specialized media outlets have the potential to encourage sports clubs to embrace professionalism in Algeria.